2017
DOI: 10.1088/1361-6463/aa9b6a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient p-n junction-based thermoelectric generator that can operate at extreme temperature conditions

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The activation energy of 1.1 ± 0.2 eV for the parallel shunt resistance Rp is much smaller than that of the saturation current density j0, which was attributed to minority carrier diffusion and with an activation energy intermediate of the band gaps of the two materials (Eg,av = 3.5 eV). We thus suggest that Rp may be related to mid-gap defect levels in the p-n-junction, as also suggested by Chavez et al for Si-based junctions [34].…”
Section: Resultssupporting
confidence: 85%
“…The activation energy of 1.1 ± 0.2 eV for the parallel shunt resistance Rp is much smaller than that of the saturation current density j0, which was attributed to minority carrier diffusion and with an activation energy intermediate of the band gaps of the two materials (Eg,av = 3.5 eV). We thus suggest that Rp may be related to mid-gap defect levels in the p-n-junction, as also suggested by Chavez et al for Si-based junctions [34].…”
Section: Resultssupporting
confidence: 85%
“…Figure b shows the replot of the J – V curve in the semilogarithmic mode for the heterojunctions, and the ideality factor is found to be ≈1.1. Since the ideality factor is close to unity, the electrical transport of the junctions is dominated by diffusion current, where recombination processes are minor. , Furthermore, the diode characteristics of the present device are improved when compared with the ones presented by Chavez et al , and Desissa et al in their bulk devices with a p–n junction without metal contact. Particularly, Chavez et al reported an inhomogeneous p–n junction due to the mixing of the nanoparticle powders prior to and during the densification step for the device fabrication.…”
Section: Results and Discussionmentioning
confidence: 53%
“…Many of these issues could be tackled by the approach of Shin et al. through the use of oxide TEs with a direct p–n junction, hereby omitting the metal interconnects at the hot side. However, p–n junctions are usually not Ohmic but exhibit rectifying behavior, which represent large parasitic resistances in the device. A solution to the rectifying behavior is a broken-gap junction couple, well-known in the field of photovoltaics. A broken-gap junction forms a charge accumulation region instead of a charge depletion zone, which leads to fully Ohmic characteristics.…”
Section: Introductionmentioning
confidence: 99%